Determination of heat transfer rates in an industry-like spray quench system using multiple impinging water jets. (7th October 2005) - Hamed, M.S.; Akmal, M.
Liquid jet impingement (LJI) cooling is widely employed in quench systems, the majority of which utilise multiple impinging jets. Successful design and operation of such systems require accurate data of actual heat transfer rates. The present study is concerned with the determination of heat transfer rates during rapid cooling of high temperature surfaces using multiple impinging water jets (MIWJs) in an industry-like arrangement. The effects of jet variables have been investigated. Heat transfer coefficients have been numerically calculated using inverse analysis, utilising experimentally determined temperature profiles. Comparison with heat transfer rates of immersion quenching has been considered. The present study provides important information about heat transfer rates in an industry-like water spray quench system using MIWJs. Results demonstrated that the use of MIWJs offers significant flexibility in controlling cooling rates, which renders this technique most suitable for quench operations requiring wide range of cooling rates.